L'utilità dello Zulliger Test nella valutazione del funzionamento psichico - 1 Concetta Vergati, 1 Simona Annunziata, 1 Gesualda Baldo, 1 Teresa Longobardi, 2 Olimpia Ricciardi, 2 Simona Verniti (Marp Edizioni, 2019)
The Zulliger Test (or Z-Test) is a projective technique elaborated by Hans Zulliger (1893-1965), both in the individual form and in the collective form. It is a psychodiagnostic instrument that, as the most famous Rorschach Test, is based on the ink spots method (or "ink-blot"), and that invites the subject to interpret symmetrical and little structured spots. Initially, it was created in the slides version for the selection of soldiers of Swiss army and successively proposed as planks for the individual administration. The following article proposes to evidence the usefulness of individual form of Z-Test in the appraisal of psychical operation, both normal and pathological. A review of the literature is lead carrying out searches of articles and witnesses through search engines PubMed, ResearchGate, Google Scholar, APA following PsycNET® by the keywords: "Zulliger test", "Hans Zulliger", "projective test". Found the usefullness of Z-Test in individual form for the appraisal of psychical operation, the necessity of a study is evidenced for the definition of the normative champion of the Italian adult normal population.